Financialisation and the fall in the labour share: a panel data econometric analysis for the European Union countries - Barradas, Ricardo (2017)
This paper conducts an empirical analysis of the relationship between financialisation and the labour share using panel data composed of 27 European Union countries over 19 years (from 1995 to 2013). Adopting a Kaleckian perspective, framed in the post-Keynesian literature, financialisation exerts a negative influence on the labour share through three different channels: the change in the sectorial composition of economies (the increasing importance of financial activity and the decreasing importance of general government activity), the proliferation of ‘shareholder value orientation’ and the deterioration of general workers’ bargaining power. We estimate a labour share equation with the traditional variables (lagged labour share, technological progress, globalisation, education and output growth) and four further measures of financialisation (financial activity, general government activity, ‘shareholder value orientation’ and the trade union density rate). The findings show a disruptive relationship between financialisation and the labour share in European Union countries, mainly through the channels of general government activity and ‘shareholder value orientation’. It is also found that financialisation has contributed to a fall in the labour share in European Union countries as a whole and more specifically in non-euro area countries, ‘bank-based’ countries and ‘coordinated market’ countries. The slowdown of output was the main driver of the fall in the labour share in European Union countries, a trend that could persist in the future taking into account the fears of potential ‘secular stagnation’ in the current era of financialisation.